Erratum: KANG, T.H., HAN, T.M., OKUSHIMA, Y. & PARK, H.C. (2012) Integrative taxonomy of Asiopodabrus fragiliformis (Kang and Kim, 2000) (Coleoptera: Cantharidae) and its related species. Zootaxa, 3259, 1–33. - Kang, T. H.; Han, T. M.; Okushima, Y.; Park, H. C. (Zootaxa, 2012)
(Erratum)